ANALYSIS OF FINANCIAL PERFORMANCE IN PT ARWANA CITRA MULIA TBK - Roy Seleky (Soso-Q : Jurnal Manajemen, 2020)
This study aims to determine and examine the financial performance achievements of PT. Arwana Citra Mulia Tbk. The analysis used is a quantitative descriptive analysis method where the analysis of financial ratios is used to detect financial performance achievements which are then interpreted in order to obtain the achievement of the company's financial performance achievements. PT Arwana Citra Mulia Tbk's financial performance has tended to be educational, where in 2014 year 2015 the analysis of the company's financial performance has decreased. 2016 began to move up to the end of the analysis, which is 2017. Which experienced a slight condition is the achievement of working capital turnover in 2014 to 2015, but after that decreased very dramatically. Based on the results of this financial ratio analysis, it was concluded that the financial performance of PT. Arwana Citra Mulia Tbk. Fluctuating with the best performance in 2015 and 2016 alone. Keyword: Financial Statement => Analysis => Financial Performances Keuangan